2021
DOI: 10.1007/s00426-020-01460-8
|View full text |Cite
|
Sign up to set email alerts
|

Information stored in memory affects abductive reasoning

Abstract: Abductive reasoning describes the process of deriving an explanation from given observations. The theory of abductive reasoning (TAR; Johnson and Krems, Cognitive Science 25:903–939, 2001) assumes that when information is presented sequentially, new information is integrated into a mental representation, a situation model, the central data structure on which all reasoning processes are based. Because working memory capacity is limited, the question arises how reasoning might change with the amount of informati… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
3
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 64 publications
1
4
0
Order By: Relevance
“…The goal of this study was to test whether exemplar retrieval also occurs during preferential judgments and to link eye movements to preferential judgments. Eye-movement measures based on the looking-at-nothing behavior have been shown to indicate exemplar retrieval from memory during inferential choice (Rosner et al, 2021;Rosner & von Helversen, 2019;Scholz et al, 2015). In line with previous research, we found that the amount people looked at empty spatial locations reflected the similarity (defined as number of matches in cue values) between test items and training exemplars.…”
Section: Discussionsupporting
confidence: 88%
“…The goal of this study was to test whether exemplar retrieval also occurs during preferential judgments and to link eye movements to preferential judgments. Eye-movement measures based on the looking-at-nothing behavior have been shown to indicate exemplar retrieval from memory during inferential choice (Rosner et al, 2021;Rosner & von Helversen, 2019;Scholz et al, 2015). In line with previous research, we found that the amount people looked at empty spatial locations reflected the similarity (defined as number of matches in cue values) between test items and training exemplars.…”
Section: Discussionsupporting
confidence: 88%
“…We reinvited participants, who took part in two reasoning experiments (29,53) one week later to the test their working memory capacity.…”
Section: Methodsmentioning
confidence: 99%
“…Similarly, mental rotation and prefrontal analysis also demand significant levels of relational reasoning, but prefrontal synthesis and abstract inference will always involve a larger amount of information to be handled since it is positively influenced by the number of asynchronous NEs involved. Furthermore, associative inference and future-oriented thought (Table 1) demonstrate the predictive nature of mental imagery, being capable of exploring available (but absent) possibilities (Cahart-Harris & Friston, 2010;Klichowicz et al, 2021Klichowicz et al, , 2022Spalding et al, 2018), while abstract inference and deductive reasoning (Table 1) display the intangible nature of relational reasoning, which allows it to generate knowledge beyond past (and thus expected) experiences (Halford, Wilson, & Phillips, 2010;Holyoak & Lu, 2021;Wu, Jung & Zhang, 2016). It's important to note that similar categorizations of imagination have been previously suggested by other researchers (Sassenberg et al, 2023;Vyshedskiy, 2019).…”
Section: Role Of Large-scale Brain Network In Imaginationmentioning
confidence: 99%
“…As previously mentioned, associative processes (e.g. free associations, daydreaming and associative inference; Table 1) are also predictive and, hence, involve an automatic exploration of available possibilities (Cahart-Harris & Friston, 2010;Klichowicz et al, 2021Klichowicz et al, , 2022Spalding et al, 2018) that opposes the objective of generating uncorrelated ideas proposed by the DT method. For example, if someone is daydreaming about going to a grocery store, imaginative experiences elicited by associative processing will be the result of the merging of past experiences and knowledge in a sort of abductive process, such as a blackout happening in that place (which is contextually coherent and useful for narrative development), rather than generating completely unprecedented ideas, like imagining yourself as being in the referred food market in the absence of gravity (Table 1).…”
Section: Individual Differences In Mental Imagery and Relational Reas...mentioning
confidence: 99%